James Gordon Bennett papers - Bennett, James Gordon, 1795-1872.
Chiefly correspondence (1861-1864) concerning the Civil War and national politics, addressed to Bennett as publisher of the New York Herald, by staff reporters located at the headquarters of Gen. George Brinton McClellan in Washington and in the field. Also includes letters addressed to Bennett's assistant and business manager, Frederic Hudson, recipient copy of a letter (1845) from Bennett to Thomas Ritchie, drafts of articles, clippings (1862-1863), and pamphlets. Correspondents include Nathaniel Prentiss Banks, James Gordon Bennett, Jr., Charles G. Halpine, Thurlow Weed, and Fernando Wood.
Microfilm edition available
Microfilm produced from originals and photocopies in the Manuscript Division.
In part, negative photocopies of originals in private hands.
Private
Newspaper publisher.
Collection material in English.
Keywords: Banks, Nathaniel Prentiss, -- 1816-1894 -- Correspondence; Bennett, James Gordon, -- 1841-1918 -- Correspondence; Halpine, Charles G. -- 1829-1868 -- Correspondence; Hudson, Frederic, -- 1819-1875 -- Correspondence; McClellan, George Brinton, -- 1826-1885.; Ritchie, Thomas, -- 1778-1854 -- Correspondence; Weed, Thurlow, -- 1797-1882 -- Correspondence; Wood, Fernando, -- 1812-1881 -- Correspondence; New York herald; American newspapers -- New York (State); United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Journalists; United States -- Politics and government -- 1861-1865.; Publishers